The question of societal security in the Arctic - Hossain, Kamrul (Routledge, 2018)
This chapter argues that societal security is not just a fight for survival, it is also about the promotion of conditions for the greater sustenance of a society – it is about 'survival plus'. It highlights the human security concept's normative utility and guiding role for the promotion of value additions and ethical norms in security debates as they relate to the formation and promotion of societal sustainability. In the case of the Barents Region, the presence of indigenous peoples and their particular context in a regional and societal scope require the integration of political processes transcending their national border lines. A definition of societal security is presented in the International Organization for Standardization. The Arctic Human Development Report has largely addressed many of these issues from the viewpoint of socio-cultural, economic and environmental aspects in order to promote community cohesion within the region.